Impact of cardiac resynchronisation therapy on burden of hospitalisations and survival: a retrospective observational study in the Northern Region of New Zealand. Issue 5 (27th May 2019) - Looi, Khang-Li; Lever, Nigel; Gavin, Andrew; Doughty, Robert
Abstract : Objective: Cardiac resynchronisation therapy (CRT) devices have been shown to improve heart failure (HF) symptoms, survival and improve quality of life (QoL). We evaluated the overall impact of CRT on recurrent hospitalisations and survival in real-world patients with HF. Design: Retrospective observational study. Setting: Northern region of New Zealand. Participants: Patients with HF who underwent CRT device implantation in between 2008 and 2014 were followed up for 1 year. Interventions: CRT. Primary and secondary outcomes measured: Survival, all-cause hospitalisations, length of stay, from which days alive and out of hospital (DAOH) were calculated. Results: 177patients were included, of whom eight died (4.5%) within 1 year of follow-up. Pre-CRT implantation, 83% of all patients had been hospitalised for a total 248 hospitalisation events. Following CRT, 47 patients (27%) were readmitted to hospital within 1 year (total of 98 admissions; p<0.01 compared with pre-device implant). Length of hospital stay was significantly shorter than in the year prior to CRT implantation at a median of 4 (IQR 2–6) vs 7 (IQR 3.5–10.5) days (p=0.03). An increase in the median number of DAOH was observed from 362 (IQR 355–364) to 365 (IQR 364–365) (p<0.01) after CRT implant. The improvement in DAOH was seen regardless of gender and type of CRT devices. Greater DAOH was also seen in those with non-ischaemic cardiomyopathy and Caucasians. Conclusion: After CRT implant, patients with HF have greater DAOH with reduction of total hospitalisation and fewer hospital days. These results support CRT devices use as a treatment option for appropriate HF patients. DAOH represents an easily measured, patient-centred endpoint that may reflect effectiveness of interventions in future CRT studies.